2006
DOI: 10.1111/j.1365-2672.2006.03110.x
|View full text |Cite
|
Sign up to set email alerts
|

The infectivity of transmissible spongiform encephalopathy agent at low doses: the importance of phospholipid

Abstract: The issue of whether the mechanism of infection is independent or co‐operative for low doses of transmissible spongiform encephalopathy (TSE) agent is critical for risk assessment. The susceptibility (and hence ID50) of individuals with the same prion protein (PrP) genotype may vary considerably with a small proportion being very susceptible. Assuming independent action, the incubation period (IP) would continue to increase until the dose is below the ID50 of the most susceptible individuals in the experiment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…(iii) Polar organic solvents that are able to extract polar lipids such 2-choroethanol inactivate prions, whereas nonpolar solvents such as hexane do not (16,17). (iv) Variations in the strength of interaction between PrP and phospholipids correlate with differences in the thermostability of various prion strains (18,19). (v) Radio inactivation studies suggest the presence of essential lipid molecules within infectious prions (20).…”
Section: Discussionmentioning
confidence: 99%
“…(iii) Polar organic solvents that are able to extract polar lipids such 2-choroethanol inactivate prions, whereas nonpolar solvents such as hexane do not (16,17). (iv) Variations in the strength of interaction between PrP and phospholipids correlate with differences in the thermostability of various prion strains (18,19). (v) Radio inactivation studies suggest the presence of essential lipid molecules within infectious prions (20).…”
Section: Discussionmentioning
confidence: 99%
“…2006), mediating specific interaction between the antigen presenting CD1d molecule and the T‐cell receptors on the NKT cell. Thus, it could be envisaged that PrP Sc /SL interactions within the TSE agent nucleation seed could be highly specific (depending on the 3D structure of PrP Sc ) accounting for the both high thermostability of the TSE agent and differences between strains in thermostability as proposed previously (Gale 2006a). In that study, IP data were interpreted in terms of the nucleation seeds in untreated material initiating infection through independent action, with treatments such as alkali and autoclaving disrupting the protein/lipid interactions and degrading the lipid, thus breaking up the nucleation seeds into smaller PrP units, or even PrP monomers, which require co‐operative interactions at low doses giving much longer IPs.…”
Section: Introductionmentioning
confidence: 79%
“…on surgical instruments). Previously, it was proposed that the unit of infectivity for prion disease is a nucleation seed comprised of PrP and host phospholipid (PL), with the strength of the protein/lipid interactions controlling the thermostability (Gale 2006a). As yet there are no data which positively identify a second component, and if a host lipid is involved, it is more likely to be host sphingolipid (SL) rather than PL.…”
Section: Introductionmentioning
confidence: 99%
“…2, Gale has shown that PS is the host-independent molecule associated with enhancing PrPSc aggregation (Gale, 2006). Robinson and Pinheiro have recently reported that PSs alter amyloid aggregation pathways by increasing aggregation (Robinson & Pinheiro, 2010), which suggests an alternative approach for therapeutic treatment of prion diseases.…”
Section: Logicmentioning
confidence: 99%
“…Gale showed that a phospholipid is most likely to be this molecule through the strain thermostability studies (Gale, 2006). Recent studies of prion diseases in membrane environments suggest that Phosphatidylserine (PS) is a molecule capable of altering amyloid aggregation pathways and increasing aggregation rates (Robinson & Pinheiro, 2010).…”
Section: Introductionmentioning
confidence: 99%